Unveiling the volatile compounds and antibacterial mechanisms of action of Cupressus sempervirens L., against Bacillus subtilis and Pseudomonas aeruginosa - Al-Mijalli, Samiah Hamad; El Hachlafi, Naoufal; Mohamed, Jeddi; Abdallah, Emad M; Assaggaf, Hamza; Qasem, Ahmed; Lee, Learn-Han *; Law, Jodi Woan-Fei; Aladhadh, Mohammed; Alnasser, Sulaiman Mohammed; Bouyahya, Abdelhakim; Mrabti, Hanae Naceiri (Elsevier, 2023)
Cupressus sempervirens is a known traditional plant used to manage various ailments, including cancer, inflammatory and infectious diseases. In this investigation, we aimed to explore the chemical profile of Cupressus sempervirens essential oil (CSEO) as well as their antibacterial mode of action. The volatile components were characterized using gas chromatography coupled to a mass spectrometer (GC-MS). The results revealed remarkable antibacterial properties of EO derived from C. sempervirens. GC-MS analysis indicated that C. sempervirens EO characterized by δ-3-carene (47.72%), D-limonene (5.44%), β-pinene (4.36%), β-myrcene (4.02%). The oil exhibited significant inhibitory effects against a range of bacteria, including Staphylococcus aureus ATCC 29213, Bacillus subtilis ATCC 13048, Bacillus cereus (Clinical isolate), Pseudomonas aeruginosa ATCC 27853, and Escherichia coli ATCC 25922. These inhibitory effects surpassed those of conventional antibiotics. Furthermore, the EO demonstrated low minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs), indicating its bactericidal nature (MBC/MIC < 4.0). Time-kill kinetics analysis showed that CSEO was particularly effective at 2 × MIC doses, rapidly reduced viable count of B. subtilis and P. aeruginosa within 8 h. This suggests that the oil acts quickly and efficiently. The cell membrane permeability test further demonstrated the impact of CSEO on the relative conductivity of B. subtilis and P. aeruginosa, both at 2 × MIC concentrations. These observations suggest that EO disrupts the bacterial membrane, thereby influencing their growth and viability. Additionally, the cell membrane integrity test indicated that the addition of CSEO to bacterial cultures resulted in the significant release of proteins from the bacterial cells. This suggests that EO affects the structural integrity of the bacterial cells. Furthermore, the anti-biofilm assay confirmed the efficacy of CSEO as a potent anti-biofilm agent. It demonstrated the oil's ability to inhibit quorum sensing, a crucial mechanism for biofilm formation, and its competitive performance compared to the tested antibiotics.